2021
DOI: 10.21203/rs.3.rs-787616/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dark Triad, Impulsivity And Honesty-Humility And Intended Behavior In A Prisoner’s Dilemma Game: A Simulation Study

Abstract: Objective: The aim of the study was to investigate if the Dark Triad personality traits, Impulsivity and Honesty-Humility can predict individuals’ intended behavior in one-shot Prisoner’s Dilemma Games (PDG). Method: A cross-sectional correlational design was followed, examining multiple linear regression models. A total sample of 197 Greek adults (64% women, M=35.13 years old) completed a one-shot simulated PDGs, the Dirty Dozen scale, the Barratt Impulsivity Scale and the Honesty-Humility subscale from the H… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In cooperative games, DT is thought to defect more than cooperate. Lainidi et al (2021) study showed that higher levels of DT traits significantly increased the chances of PROSOCIALITY AND THE DARK TRIAD 7 defection in a prisoner's dilemma game. Malesza (2020) found that psychopathy and Machiavellianism were linked to higher rates of defection in an iterative prisoner's dilemma game.…”
Section: Defection and Co-operation In The Dark Triadmentioning
confidence: 93%
“…In cooperative games, DT is thought to defect more than cooperate. Lainidi et al (2021) study showed that higher levels of DT traits significantly increased the chances of PROSOCIALITY AND THE DARK TRIAD 7 defection in a prisoner's dilemma game. Malesza (2020) found that psychopathy and Machiavellianism were linked to higher rates of defection in an iterative prisoner's dilemma game.…”
Section: Defection and Co-operation In The Dark Triadmentioning
confidence: 93%